Density of heavy hole states of Hg₁-xCdxTe in an isotropic nonparabolic approximation by exact measurements of electron concentration - Bogoboyashchyy, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
High precision measurements of intrinsic electron concentration ni in Hg₁₋xCdxTe crystals were made in broad ranges of compositions (x = 0…0.31) and temperatures (T = 77…420 К). It was found that effective mass of the integral heavy hole state density essentially depends on temperature. It can be explained using the conception of the non-parabolic band. The proposed model enabled to determine the differential state density in the band being based on the results of measurements. It was found that the heavy hole dispersion law at ε < 0.15 eV have the relativistic form in the framework of the measurements accuracy, where and eV for all studied compositions x. It was also shown that intrinsic electron concentration in CdTe at high temperatures (higher than 800 K), calculated with the found heavy hole state density, agrees quantitatively with known experimental data.